Data in Doctoral Research in Social Sciences: A Case Study of Karnataka - Ramesha; Asundi, A. Y.; Chand, B. B.; Chaithra, A. M. (Journal of Information and Knowledge, 2021)
Data are assuming new magnitude, since the concept of big data emerged. Data is a prominent component in social science research. The Social Science data are variable in nature from region to region. The nature of social sciences data was compared to ‘iceberg’ by DEVSIS and its capture and management was given importance. A project was undertaken on Research Data Management in social sciences focusing on use of data in doctoral research. The study covers five premier universities of Karnataka has observed clear distinct features of data in the disciplines of social sciences. Researchers from Sociology, Economics, Commerce and Management disciplines use tables and figures heavily to present research data, whereas History, Geography use visual data. The uses of data are low in disciplines like History, Political science, Law and Women’s studies. The amount of data generated by doctoral researchers has immense potential for re-packaging and reuse. It is essential to build a data repository platform to share and reuse research data and train researchers to compile and upload the data for future use.